Indonesia-Madagascar partnership in agricultural linkages (impartial) aims for sustainability - Widodo, Y; Harnowo, D; Gasikara, H; Malala, A (International Journal of Agricultural Research, Innovation and Technology, 2017)
Starting in 2011 Japan International Cooperation Agency (JICA) through the Program of Third Country Experts (TCE) invited Indonesian scientists to be involved in the development endeavors for African Countries, including Madagascar especially in attempt to increase productivity of rice as main staple food of Malagasy. Initiation of bilateral cooperation between Indonesia and Madagascar had been stimulated from JICA-TCE, furthermore for developing Indonesian soybean to Madagascar from 2013 to 2015. Madagascar and many African Countries are grouped into the countries requesting global aid for taming hunger as declared under Millennium Development Goals (MDGs) ended 2015 that continued into Sustainable Development Goals (SDGs) 2030. Fortunately, there is a similarity of languages in Indonesia and Madagascar East and West Africa as heritage from the ancient voyage before western occupation or even Before Christ (BC) era as reflected in the relief at wall of Borobudur a Buddhist temple in Magelang Central Java Indonesia. Based on historical background, there is an opportunity to propose Indonesia- Madagascar Partnership in Agricultural Linkages (IMPARTIAL) as a new alliance for attaining sustainable development in developing countries at the southern hemisphere. Implementing agricultural innovation to provide adequate food and renewable energy for daily modern livelihood is a key to attain sustainability. Int. J. Agril. Res. Innov. & Tech. 7 (1): 21-31, June, 2017